Zirconium oxide material as well as preparation method and application thereof
By adding alumina whiskers and dispersant to the zirconia powder and using ultrasonic dispersion and discharge plasma sintering processes, the problem of insufficient toughness of zirconia ceramic materials is solved, and zirconia materials with ultra-high toughness and high hardness are prepared, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411456420.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-03-04
AI Technical Summary
Zirconia ceramic materials have low toughness and are prone to breakage, which limits their application in 3C product appearance components and crown body materials.
By mixing the zirconia powder with alumina whiskers, dispersants and solvents, a suspension is formed, and ultrasonic dispersed and dried, and then zirconia material is prepared by discharge plasma sintering process.
The toughness of zirconia materials is improved, with a toughness above 13.94MPa m1/2, while maintaining high hardness. It is suitable for 3C product appearance components and crown main materials.
Smart Images

Figure CN119551996A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and specifically relates to a zirconium oxide material and a preparation method and application thereof. Background Art
[0002] Zirconia is a structural ceramic material. Due to its high hardness, low density, corrosion resistance and good electromagnetic wave penetration performance, it is widely used in 3C product appearance components, crown main body materials, etc. However, compared with metal materials, the toughness of zirconia ceramics is still relatively low, showing greater brittleness and easy breakage, which limits the further application of zirconia ceramic materials. In the prior art, zirconium oxide or zirconium oxide-based composite materials are usually prepared by ball milling zirconium oxide and additives, and then sintering in a muffle furnace. However, the toughness of zirconium oxide or zirconium oxide-based composite materials prepared by this method is poor. Therefore, how to improve the toughness of zirconia materials has become a difficult problem in the prior art. Summary of the invention
[0003] The object of the present invention is to provide a zirconium oxide material and a preparation method and application thereof. The zirconium oxide material prepared by the preparation method provided by the present invention has ultra-high toughness.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a zirconium oxide material, comprising the following steps:
[0006] (1) mixing zirconium oxide powder with aluminum oxide whiskers, a dispersant and a solvent to obtain a suspension; the dispersant comprises one or more of KOS110, BYK110 and KOS163;
[0007] (2) subjecting the suspension obtained in step (1) to ultrasonic dispersion and drying to obtain a mixed powder;
[0008] (3) The mixed powder obtained in step (2) is subjected to spark plasma sintering to obtain zirconium oxide material.
[0009] Preferably, in step (1), the length of the aluminum oxide whisker is 0.5 to 5 μm, and the diameter of the aluminum oxide whisker is 10 to 100 nm.
[0010] Preferably, in step (1), the mass ratio of alumina whiskers to zirconium oxide powder is (0.05-0.15):1.
[0011] Preferably, in step (1), the mass ratio of the dispersant to the zirconium oxide powder is (0.001-0.05):1.
[0012] Preferably, the solvent in step (1) comprises one or more of acetone, ethanol and N,N-dimethylformamide.
[0013] Preferably, the mass content of zirconium oxide powder in the suspension in step (1) is 35-45%.
[0014] Preferably, the power of ultrasonic dispersion in step (2) is 400-600 W, and the time of ultrasonic dispersion is 20-40 min.
[0015] Preferably, in step (3), the spark plasma sintering temperature is 1300-1350° C., the spark plasma sintering time is 3-6 min, and the spark plasma sintering pressure is 25-50 MPa.
[0016] The present invention also provides a zirconium oxide material prepared by the preparation method described in the above technical solution.
[0017] The present invention also provides the application of the zirconium oxide material described in the above technical solution in 3C product appearance components and crown main body materials.
[0018] The present invention provides a method for preparing a zirconium oxide material, comprising the following steps: (1) mixing zirconium oxide powder with aluminum oxide whiskers, a dispersant and a solvent to obtain a suspension; the dispersant comprises one or more of KOS110, BYK110 and KOS163; (2) subjecting the suspension obtained in the step (1) to ultrasonic dispersion and then drying to obtain a mixed powder; and (3) subjecting the mixed powder obtained in the step (2) to spark plasma sintering to obtain the zirconium oxide material. The present invention adds alumina whiskers and utilizes the deflection effect of alumina whiskers on cracks. Alumina whiskers will change the direction of crack expansion, increase crack expansion energy, and effectively inhibit crack expansion, thereby improving toughness; a dispersant is added and the type of dispersant is controlled. A specific type of dispersant can evenly wrap the alumina whiskers and zirconium oxide powder, reduce agglomeration, improve uniformity, and give full play to the crack deflection effect of the whiskers; ultrasonic dispersion of the suspension can evenly disperse the alumina whiskers in the zirconium oxide powder matrix without destroying the structure of the alumina whiskers, giving full play to the crack deflection effect of the alumina whiskers; spark plasma sintering can improve the material density, reduce the grain size, improve toughness, and greatly shorten the preparation time during the sintering process. The results of the embodiment show that the toughness of the zirconium oxide material prepared by the preparation method of the present invention is 13.94MPam. 1 / 2 above. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a SEM image of the aluminum oxide whisker in Example 2 of the present invention;
[0020] Figure 2The hardness and toughness test indentations of the zirconium oxide material prepared in Example 2 of the present invention;
[0021] Figure 3 This is a SEM image of the zirconium oxide material prepared in Example 2 of the present invention at a magnification of 1000 times;
[0022] Figure 4 This is a SEM image of the zirconium oxide material prepared in Example 2 of the present invention at a magnification of 15,000 times. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing a zirconium oxide material, comprising the following steps:
[0024] (1) mixing zirconium oxide powder with aluminum oxide whiskers, a dispersant and a solvent to obtain a suspension; the dispersant comprises one or more of KOS110, BYK110 and KOS163;
[0025] (2) subjecting the suspension obtained in step (1) to ultrasonic dispersion and drying to obtain a mixed powder;
[0026] (3) The mixed powder obtained in step (2) is subjected to spark plasma sintering to obtain zirconium oxide material.
[0027] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0028] The invention mixes zirconium oxide powder with aluminum oxide whiskers, a dispersant and a solvent to obtain a suspension.
[0029] In the present invention, the particle size of the zirconium oxide powder is preferably 90-110 nm, more preferably 100 nm. The present invention limits the particle size of the zirconium oxide powder to the above range, so that it can be mixed with other raw materials more evenly, further improving the toughness of the zirconium oxide material.
[0030] In the present invention, the length of the aluminum oxide whisker is preferably 0.5 to 5 μm, more preferably 2 to 3 μm; the diameter of the aluminum oxide whisker is preferably 10 to 100 nm.
[0031] In the present invention, the mass ratio of the alumina whisker to the zirconium oxide powder is preferably (0.05-0.15): 1, and more preferably (0.05-0.10): 1. The length, diameter and amount of the alumina whisker are limited within the above ranges, which can better play the crack deflection effect of the alumina whisker and further improve the toughness of the zirconium oxide material. However, excessive use of the alumina whisker will increase defects in the zirconium oxide powder matrix and reduce toughness.
[0032] In the present invention, the dispersant includes one or more of KOS110, BYK110 and KOS163, preferably KOS110. Compared with other dispersants, the present invention uses the above-mentioned specific type of dispersant to evenly wrap the alumina whiskers and the zirconium oxide powder, reduce agglomeration, improve the uniformity of the mixed powder, give full play to the crack deflection effect of the whiskers, and further improve the toughness and other properties of the zirconium oxide material.
[0033] In the present invention, the mass ratio of the dispersant to the zirconium oxide powder is preferably (0.001-0.05): 1, more preferably (0.01-0.03): 1, and further preferably 0.015: 1. The present invention limits the mass ratio of the dispersant to the zirconium oxide powder to the above range, which can further improve the toughness and other properties of the zirconium oxide material.
[0034] In the present invention, the solvent preferably includes one or more of acetone, ethanol and N,N-dimethylformamide, and more preferably acetone. The present invention has no special limitation on the amount of the solvent, as long as the mass content of the zirconium oxide powder in the suspension is within a limited range.
[0035] In the present invention, the mass content of zirconium oxide powder in the suspension is preferably 35-45%, more preferably 40%. The present invention limits the mass content of zirconium oxide powder in the suspension to the above range, so that each component can be fully dispersed.
[0036] After obtaining the suspension, the present invention performs ultrasonic dispersion on the suspension and then dries it to obtain a mixed powder.
[0037] In the present invention, the power of the ultrasonic dispersion is preferably 400-600W; the time of the ultrasonic dispersion is preferably 20-40min, more preferably 30min. Compared with ball milling, the ultrasonic dispersion of the present invention can evenly disperse the alumina whiskers in the zirconium oxide powder matrix without destroying the structure of the alumina whiskers, giving full play to the crack deflection effect of the alumina whiskers. The power and time of the ultrasonic dispersion are limited to the above range, so that the components can be mixed more fully.
[0038] The present invention has no special limitation on the drying operation, as long as the solvent is completely evaporated.
[0039] After obtaining the mixed powder, the present invention performs spark plasma sintering on the mixed powder to obtain the zirconium oxide material.
[0040] In the present invention, the temperature of the spark plasma sintering is preferably 1300-1350°C; the time of the spark plasma sintering is preferably 3-6 minutes, more preferably 5 minutes; the pressure of the spark plasma sintering is preferably 25-50MPa, more preferably 30-40MPa; the heating rate to the spark plasma sintering temperature is preferably 90-110°C / min, more preferably 100°C / min. The present invention uses spark plasma sintering to apply pressure during the sintering process to increase the density of the material, reduce the grain size, improve the toughness, and shorten the preparation time. The present invention limits the parameters of spark plasma sintering within the above range, which can further improve the toughness of the zirconia material.
[0041] After the spark plasma sintering is completed, the present invention preferably cools the product of the spark plasma sintering to obtain a zirconium oxide material.
[0042] The present invention has no special limitation on the cooling operation, and cooling to room temperature may be performed using cooling technical solutions well known to those skilled in the art.
[0043] The invention adds aluminum oxide whiskers and utilizes the deflection effect of the aluminum oxide whiskers on cracks to improve toughness; adds a dispersant and controls the type of the dispersant to reduce agglomeration, improve uniformity, and give full play to the crack deflection effect of the whiskers; adopts ultrasonic dispersion to evenly disperse the aluminum oxide whiskers in a zirconium oxide powder matrix without destroying the structure of the aluminum oxide whiskers; adopts spark plasma sintering to apply pressure during the sintering process to improve the material density, reduce the grain size, improve the toughness, and greatly shorten the preparation time; and controls various process parameters to obtain a zirconium oxide material with ultra-high toughness.
[0044] The present invention also provides a zirconium oxide material prepared by the preparation method described in the above technical solution.
[0045] The zirconia material prepared by the invention comprises a zirconia matrix and aluminum oxide whiskers dispersed in the zirconia matrix.
[0046] The zirconia material prepared by the present invention has high hardness and ultra-high toughness, with a hardness of more than 14GPa and a toughness of more than 13.5MPa m 1 / 2 .
[0047] The present invention also provides the application of the zirconium oxide material described in the above technical solution in 3C product appearance components and crown main body materials.
[0048] The present invention has no special limitation on the operation of the application, and the technical solutions of the application well known to those skilled in the art may be adopted.
[0049] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] Example 1
[0051] (1) Zirconia powder (particle size 100 nm), alumina whiskers (length 2 μm, diameter 50 nm), dispersant KOS110 (Guangzhou Kangou Shuang Trading Co., Ltd.) and acetone were mixed to obtain a suspension, wherein the mass content of the zirconium oxide powder in the suspension was 40%, the mass ratio of the alumina whiskers to the zirconium oxide powder was 0.05:1, and the mass ratio of the dispersant KOS110 to the zirconium oxide powder was 0.015:1;
[0052] (2) using an ultrasonic disperser to ultrasonically disperse the suspension obtained in step (1) at an ultrasonic power of 500 W and an ultrasonic time of 30 min. After the ultrasonic dispersion is completed, the suspension is heated and stirred to volatilize the acetone to obtain a mixed powder;
[0053] (3) Weigh 1.5 g of the mixed powder obtained in step (2) and put it into a graphite mold with a diameter of 10 mm. Then put the mold into a spark plasma sintering furnace for spark plasma sintering. The heating rate is 100°C / min, the spark plasma sintering temperature is 1320°C, the holding time is 5 min, the pressure is 30 MPa, and the zirconium oxide material is taken out after cooling.
[0054] Example 2
[0055] The mass ratio of alumina whiskers to zirconium oxide powder in step (1) of Example 1 was replaced with 0.1:1, and the other parameters were the same as those in Example 1.
[0056] Example 3
[0057] The mass ratio of alumina whiskers to zirconium oxide powder in step (1) of Example 1 was replaced with 0.15:1, and the other parameters were the same as those in Example 1.
[0058] Comparative Example 1
[0059] Zirconia powder (particle size 100nm) is placed in a graphite mold with a diameter of 10mm, and then the mold is placed in a spark plasma sintering furnace for spark plasma sintering. The heating rate is 100℃ / min, the spark plasma sintering temperature is 1320℃, the holding time is 5min, the pressure is 30MPa, and the zirconium oxide material is obtained after cooling.
[0060] Comparative Example 2
[0061] Zirconia powder (particle size 100 nm) was placed in a muffle furnace for sintering at a temperature of 1320° C., a heating rate of 5° C. / min, and a holding time of 2 h. After cooling, the zirconium oxide material was obtained.
[0062] Comparative Example 3
[0063] (1) ball-milling zirconium oxide powder (particle size 100 nm) and aluminum oxide whiskers (length 2 μm, diameter 50 nm), wherein the mass ratio of aluminum oxide whiskers to zirconium oxide powder is 0.05:1, to obtain a mixed powder;
[0064] (2) Weigh 1.5 g of the mixed powder obtained in step (1) and put it into a muffle furnace for sintering at a temperature of 1320° C., a heating rate of 5° C. / min, and a holding time of 2 h. After cooling, take out the mixed powder to obtain a zirconium oxide material.
[0065] Comparative Example 4
[0066] The mass ratio of alumina whiskers to zirconium oxide powder in step (1) of Example 1 was replaced with 0.2:1, and the other parameters were the same as those in Example 1.
[0067] Comparative Examples 5 to 8
[0068] The dispersant KOS110 in Example 1 was replaced by Lubrion solsperse 41000, BYKJET9131, Lubrion solsperse 43000 and Sasol novelution S70, respectively.
[0069] The dispersants in Comparative Examples 5 to 8 were unable to disperse the powder uniformly, resulting in the suspension being unable to pass smoothly through the filter paper with a pore size of 3 microns.
[0070] Comparative Examples 9 to 10
[0071] The mass ratios of the dispersant KOS110 and the zirconium oxide powder in Example 1 were replaced with 0.06:1 and 0.0005:1, respectively.
[0072] In Comparative Examples 9 to 10, changing the amount of dispersant also resulted in the inability to evenly disperse the powder, resulting in the inability of the suspension to smoothly pass through the filter paper with a pore size of 3 microns.
[0073] The aluminum oxide whiskers in Example 2 were observed using a scanning electron microscope, and the obtained SEM image is as follows: Figure 1 As shown. Figure 1 It can be seen that the length and diameter of the aluminum oxide whiskers.
[0074] The hardness and toughness test indentations of the zirconia material prepared in Example 2 are as follows Figure 2As shown, the toughness of the material can be calculated based on the indentation size and crack size.
[0075] The suspension in step (1) of Example 2 can pass through the filter paper with a pore size of 3 microns, which proves that it has excellent dispersibility. The zirconium oxide material prepared in Example 2 was observed using a scanning electron microscope, and the SEM images obtained at different magnifications are as follows: Figures 3-4 As shown, Figure 3 The magnification is 1000. Figure 4 The magnification is 15000. Figure 3 and Figure 4 It can be seen that the alumina whiskers are well dispersed and the cracks are deflected at the whiskers, which is the main reason for the improvement of the toughness of the zirconia material.
[0076] The hardness of the zirconium oxide materials in Examples 1 to 3 and Comparative Examples 1 to 4 was tested using a Vickers hardness tester with a test weight of 20 kg. The toughness of the material was calculated based on the size of the hardness indentation and the crack size. The results are shown in Table 1.
[0077] Table 1 Hardness and toughness of zirconium oxide materials in Examples 1 to 3 and Comparative Examples 1 to 4
[0078]
[0079] It can be seen from Table 1 that the hardness and toughness of the zirconia material are improved by adding alumina whiskers and adopting ultrasonic dispersion and spark plasma sintering in the present invention. However, when the content of alumina whiskers is too high, the toughness is reduced.
[0080] In summary, the present invention controls the preparation process to obtain a zirconium oxide material with ultra-high toughness and high hardness.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a zirconium oxide material, comprising the following steps: (1) mixing zirconium oxide powder with aluminum oxide whiskers, a dispersant and a solvent to obtain a suspension; the dispersant comprises one or more of KOS110, BYK110 and KOS163; (2) subjecting the suspension obtained in step (1) to ultrasonic dispersion and drying to obtain a mixed powder; (3) The mixed powder obtained in step (2) is subjected to spark plasma sintering to obtain zirconium oxide material.
2. The preparation method according to claim 1, characterized in that: In the step (1), the length of the aluminum oxide whisker is 0.5 to 5 μm, and the diameter of the aluminum oxide whisker is 10 to 100 nm.
3. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the aluminum oxide whisker to the zirconium oxide powder is (0.05-0.15):
1.
4. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the dispersant to the zirconium oxide powder is (0.001-0.05):
1.
5. The preparation method according to claim 1, characterized in that: The solvent in step (1) includes one or more of acetone, ethanol and N,N-dimethylformamide.
6. The preparation method according to claim 1, characterized in that: The mass content of zirconium oxide powder in the suspension of step (1) is 35-45%.
7. The preparation method according to claim 1, characterized in that: The power of ultrasonic dispersion in step (2) is 400-600W, and the time of ultrasonic dispersion is 20-40min.
8. The preparation method according to claim 1, characterized in that: In the step (3), the spark plasma sintering temperature is 1300-1350° C., the spark plasma sintering time is 3-6 minutes, and the spark plasma sintering pressure is 25-50 MPa.
9. The zirconium oxide material prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the zirconium oxide material according to claim 9 in 3C product appearance components and dental crown main body materials.